Danos existenciais e sua dimensão afetivo-familiar : tutela da dignidade da pessoa humana ou precificação do afeto? - Eick, Luciana Gemelli (2015)
The present study describes the types of material damages and analyzes the immaterial damages based on its three concepts: the traditional, the critical and the constitutional-civil concept. This study also explains the emergence and the concept of existential damages, as well as its timid application in Brazilian Law. This dissertation aims to demonstrate the development of the above mentioned legal institute and the importance of its study, so that the different types of damages can be better categorized in Brazilian law. In the second part of this study, we sought to develop a legal-critical reflection on the civil liability caused by existential damage and its applicability on Brazilian Family Law, especially with regard to the affective relations between parents and children. In these terms, the present study has the specific objective to analyze the duties dictated by Law and the duties dictated by Morals, with the intent to define the limits of the Law on basis of the coercion of human actions. Bibliographical references and legal precedents were used as research tools in this investigation.